Praktik Penghindaran Pajak di Tengah Pandemi Covid-19 - Ida Zuhaida (Yayasan Literasi Ilmiah Indonesia, 2022)
Purpose: This study was conducted to prove the effect of return on assets, leverage and the audit committee on tax avoidance Method: The method used in this research is purposive sampling using the annual financial statements of 48 companies. Finding: In this study it was found that return on assets has a positive effect on tax avoidance, leverage has a negative effect on tax avoidance and the audit committee has no effect on tax avoidance. Novelty: The update in this research is that the research was carried out during the COVID-19 pandemic